2016
DOI: 10.1038/srep36306
|View full text |Cite
|
Sign up to set email alerts
|

Manganese-mediated acceleration of age-related hearing loss in mice

Abstract: Despite the fact that manganese (Mn) is known to be a neurotoxic element relevant to age-related disorders, the risk of oral exposure to Mn for age-related hearing loss remains unclear. In this study, we orally exposed wild-type young adult mice to Mn (Mn-exposed WT-mice) at 1.65 and 16.50 mg/L for 4 weeks. Mn-exposed WT-mice showed acceleration of age-related hearing loss. Mn-exposed WT-mice had neurodegeneration of spiral ganglion neurons (SGNs) with increased number of lipofuscin granules. Mn-exposed WT-mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 43 publications
3
15
0
Order By: Relevance
“…These results partially correspond to the results of our previous study showing that all frequencies of hearing were affected in a genetically engineered mouse model of age-related hearing loss and in mice orally exposed to toxic elements, while frequencies of hearing loss in control mice were limited to higher frequencies 14, 15 . Thus, it is possible that oral exposure to As accelerates the onset of age-related hearing loss in young people.…”
Section: Discussionsupporting
confidence: 90%
“…These results partially correspond to the results of our previous study showing that all frequencies of hearing were affected in a genetically engineered mouse model of age-related hearing loss and in mice orally exposed to toxic elements, while frequencies of hearing loss in control mice were limited to higher frequencies 14, 15 . Thus, it is possible that oral exposure to As accelerates the onset of age-related hearing loss in young people.…”
Section: Discussionsupporting
confidence: 90%
“…As levels in biological samples including toenails and urine were measured by inductively coupled plasma mass spectrometry (ICP-MS; Agilent 7500cx) as described previously [ 14 , 22 , 23 ]. In brief, toenails were washed with detergent water.…”
Section: Methodsmentioning
confidence: 99%
“…In experimental studies, oral exposure to As has been shown to cause several health risks including carcinogenesis [ 20 ] and cardiovascular diseases [ 21 ]. Levels of toxic elements in inner ears, which are known to be the sensory organ for hearing, have been determined to demonstrate the correlation with hearing loss [ 22 , 23 ]. Exposure of guniea pigs to As at 200 mg/L via intraperitoneal injection for 2 months resulted in morphological impairments of the inner ear [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The specimens were observed under a fluorescent microscope (Leica DMI6000B). The software program WinROOF (Mitani Corp., Fukui, Japan) was used for immunohistochemical estimation of positive cells detected by antibodies as previously reported (Ohgami et al, 2016a ). A total of 9 serial sections from 3 mice per group were used for the estimation.…”
Section: Methodsmentioning
confidence: 99%